Prognostic Indicators of Oral Squamous Cell Carcinoma - Suresh, Girish Mysore (Ann Maxillofac Surg, 2019)
BACKGROUND: Oral squamous cell carcinoma (OSCC) is the sixth most common malignancy worldwide and is the major public health problem in the Indian subcontinent, where it ranks among the top three types of cancer in the country. Here, we aimed to analyze the clinical and tumor characteristics which impact the survival of OSCC patients. METHODS: A retrospective analysis of clinical records of all patients who underwent treatment for OSCC at Kidwai Memorial Institute of Oncology, between January 2009 and January 2012 was analyzed. Age, gender, site of the primary lesion, tumor size (T), nodal status (N), stage of the disease, marginal status, and modality of treatment data were collected and analyzed. RESULTS: Data of 147 patients with OSCC were included in the study and analyzed. Of the patients analyzed 61% were male, with 56% were <65 years, and 40% presented with buccal mucosa cancer followed by 30% with tongue cancer. Of all patients, 30% of them presented with Stage 1 and rest were Stage 2 and above. In our study, 40% underwent surgery only followed by regular follow-up and 60% needed surgery with postoperative adjuvant treatment based on the marginal status, the lymph node status, and T status of the disease. CONCLUSION: Our data suggest that age <65 years, female patients, alveolus lesion and tongue lesion and the early T Stage and N0 and negative margin had a significant positive impact on disease-free and overall survival of oral cancer patients.